Towards a multiple-scenario approach for walkability assessment: an empirical application in Shenzhen, China - Chan, ETH; Schwanen, T; Banister, D (Elsevier, 2021)
In this paper, we propose to use a relational lens to understand walkability by acknowledging that what constitutes a walkable environment may vary considerably between pedestrians who have different needs, capacities, and purposes. A multiple-scenario approach is developed for assessing walkability, which recognises that in valuation, major components in walkability assessment may not always compensate each other. The analysis accommodates the idea that some components may be so important to certain people or in particular situations that they act as hard and non-negotiable constraints on valuation. Other components, however, are negotiable and lower scores can be compensated by, and traded against, higher scores on others. The procedures for applying the multiple-scenario approach to a rapidly developing city in China are presented, using an environmental audit and reliability tests with data collected from four neighbourhoods of Shenzhen. The proposed approach offers an innovative way to account for different situations of assessing walkability, and challenges the traditional assumption of walkability by creating multiple scenarios that cater for the specific needs and preferences of pedestrians.